Attention, Media and Fuel Efficiency - Stefan Thoenes; Timo Gores (Institute of Energy Economics at the University of Cologne (EWI), 2012)
This study examines attention effects in the market for hybrid vehicles. We show that local media coverage, gasoline price changes and unprecedented record gasoline prices have a significant causal impact on the consumers' attention. As attention is not directly observable, we analyze online search behavior as a proxy for the revealed consumer attention. Our study is based on weekly panel data of local newspaper coverage, gasoline prices and Google search trends for 19 metropolitan areas in the US. Additionally, we use monthly state-level panel data to show that the adoption rate of the hybrid vehicle technology is robustly related to our measure of attention.
Keywords: D12; D83; L62; Q41; 330; consumer behavior; attention; media; gasoline price; energy efficiency; hybrid vehicle